Double Implementation in a Market for Indivisible Goods with a Price Constraint - Helmuts Azacis (Cardiff University, Cardiff Business School, 2005)
I consider the problem of assigning agents to indivisible objects, in which each agent pays a price for his object and all prices sum to a given constant. The objective is to select an assignment-price pair that is envy-free with respect to the agents' true preferences. I propose a simple mechanism whereby agents announce valuations for all objects and an envy-free allocation is selected with respect to these announced preferences. I prove that the proposed mechanism implements both in Nash and strong Nash equilibrium the set of true envy-free allocations.
Keywords: C78; C71; D78; 330; Indivisible Goods; Envy-Freeness; Implementation; Strong Nash Equilibrium